EXPLORING THE INTERFACE BETWEEN COMPLEMENTARY MEDICINE AND COMMUNITY PHARMACY IN MALAYSIA – A SURVEY OF PHARMACISTS - Pei Nee Wong; Lesley A. Braun; Thomas Paraidathathu (Malaysian Journal of Public Health Medicine, 2018)
The use of complementary medicine (CM) is on the rise worldwide. In Malaysia, CM is available as over-the-counter products in community pharmacies and consumers expect pharmacists to be knowledgeable about CM. However, little is known about Malaysian community pharmacists’ attitude and knowledge of CM. This cross-sectional study aimed to investigate the extent of integration of CM into practice, taking into account community pharmacists’ attitudes towards CM, their role in recommending CM, their knowledge of the evidence-base for commonly used CM, further education and training needs, and knowledge of information sources which can be used by pharmacists for CM information. Ethics approval was obtained and a pilot study was conducted to validate the questionnaire. After amendments were made, community pharmacists were invited to complete a 41-item paper-based or web-based questionnaire. Invitations to complete the survey were sent by either social media, email or face-to-face invitation. A response rate of 27% (453/1662) was achieved providing data from 453 community pharmacists. Most respondents were female (63%), aged 24-72 years. Only 42% of pharmacists always asked their customers presenting with a prescription about concomitant CM use. Forty-two percent (42%) of pharmacists personally recommended CM and slightly more than half (58%) had notified manufacturers of CM products of any suspected adverse drug reactions. On average, pharmacists achieved a score of 54% for knowledge on CM-drug interactions and 71% for knowledge of clinically proven benefits. Most pharmacists (75%) obtained their CM product training through self-directed learning. In addition, most pharmacists (66%) supported CM education at the undergraduate level and almost all (94%) recognised the need for additional CM education for pharmacists. Malaysian registered pharmacists do not routinely ask customers about CM use, or recommend CM products, but have a positive attitude towards their use and were interested in learning more about CM.